Pengaruh Persepsi Kegunaan dan Kemudahan Penggunaan Pada Minat Penggunaan Quick Response Code dalam Transaksi Keuangan - Aulia, Nabilah; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2019)
This research was conducted on students of the Accounting Department of FEB, Udayana University, 2015 -2018 who are still active. A sample of 294 students. The sampling technique is incidental sampling. The aim is to determine the effect of perceived usefulness and perceived ease of use on the interest of FEB Accounting Students at Udayana University in using the QR Code in financial transactions. The results of the study can be seen that there is a direct influence between the perceived ease of use on the perception of usability and also there is a direct influence between the perceived ease of use in interest in use. In this study also obtained results that there is no direct influence between perceived usefulness in interest in use and there is no influence between perceptions of ease of use in interest in use through the perception of usability as a mediator. Keywords : Perception of usability,  Perception of ease of use, interest in use, QR Code.